2022
DOI: 10.1007/s00441-022-03597-x
|View full text |Cite
|
Sign up to set email alerts
|

Disparate progenitor cell populations contribute to maintenance and repair neurogenesis in the zebrafish olfactory epithelium

Abstract: Olfactory sensory neurons (OSNs) undergo constant turnover under physiological conditions but also regenerate efficiently following tissue injury. Maintenance and repair neurogenesis in the olfactory epithelium (OE) have been attributed to the selective activity of globose (GBCs) and horizontal basal cells (HBCs), respectively. In zebrafish, cells with GBC-like properties are localized to the peripheral margins of the sensory OE and contribute to OSN neurogenesis in the intact OE, while cells that resemble HBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(58 citation statements)
references
References 87 publications
3
54
0
1
Order By: Relevance
“…OSNs undergo rapid degeneration upon nasal irrigation with the detergent Triton X-100 (TrX; Iqbal and Byrd-Jacobs, 2010), which reaches a peak at 24 h post lesion (hpl) and is followed by gradual repopulation of the OE with HuC/D-positive sensory neurons over a consecutive 4 to 6 d period. Analysis of RNAseq data (Kocagöz et al, 2022; additional data included in this study) revealed that genes typically expressed by OSNs are downregulated over the first 24 hpl but show partial or full recovery by 120 hpl, consistent with the degeneration and reestablishment of OSNs over the same period (Figure 1A). Expression of the general neuronal markers embryonic lethal abnormal visual system-like 3 (elavl3; HuC), microtubule-associated protein 2 (map2), and neuronal cell adhesion molecule 1b (ncam1b) is lowest at 24 hpl but rebounds to pre-injury levels by 120 hpl.…”
Section: Transcriptional Changes In the Lesioned Zebrafish Oesupporting
confidence: 64%
See 4 more Smart Citations
“…OSNs undergo rapid degeneration upon nasal irrigation with the detergent Triton X-100 (TrX; Iqbal and Byrd-Jacobs, 2010), which reaches a peak at 24 h post lesion (hpl) and is followed by gradual repopulation of the OE with HuC/D-positive sensory neurons over a consecutive 4 to 6 d period. Analysis of RNAseq data (Kocagöz et al, 2022; additional data included in this study) revealed that genes typically expressed by OSNs are downregulated over the first 24 hpl but show partial or full recovery by 120 hpl, consistent with the degeneration and reestablishment of OSNs over the same period (Figure 1A). Expression of the general neuronal markers embryonic lethal abnormal visual system-like 3 (elavl3; HuC), microtubule-associated protein 2 (map2), and neuronal cell adhesion molecule 1b (ncam1b) is lowest at 24 hpl but rebounds to pre-injury levels by 120 hpl.…”
Section: Transcriptional Changes In the Lesioned Zebrafish Oesupporting
confidence: 64%
“…Unlike mammals, the zebrafish OE contains multiple morphologically and molecularly distinct OSN subtypes, of which the olfactory receptor/trace amine-associated-(OR/TAAR-) expressing ciliated and the V2R-(= OlfC-) expressing microvillous cells are the most abundant (Sato et al, 2005;Korsching, 2020). Ciliated OSNs appear to recover more efficiently than apically located microvillous and the fish-specific crypt (ora4a), pear (adora2c), and ompa-or ora1-expressing chemosensory cells as indicated by the temporal expression profiles of cell type-specific marker genes (Sato et al, 2005 The tissue response to injury is characterized by an early activation of HBCs, which generate a transient population of ascl1-positive GBC-like progenitors as regenerative OSN neurogenesis unfolds (Kocagöz et al, 2022). At the transcriptional level, the HBC markers keratin4 (krt4) and krt5 are highly upregulated (3.9 ± 0.1-and 6.7 ± 2.0-fold, respectively) at 24 hpl consistent with HBC activation and increased cell proliferation (Figure 1B).…”
Section: Transcriptional Changes In the Lesioned Zebrafish Oementioning
confidence: 99%
See 3 more Smart Citations